1990
DOI: 10.1289/ehp.9086327
|View full text |Cite
|
Sign up to set email alerts
|

Surface and bulk infrared modes of crystalline and amorphous silica particles: a study of the relation of surface structure to cytotoxicity of respirable silica.

Abstract: Surface IR (infrared) modes of crystalline and fumed (amorphous) silica particles, calcined at temperatures up to 1095 degrees C, have been studied by Fourier transform infrared spectroscopy. The ability of these same particles to lyse cells has been measured by a hemolysis protocol. The untreated crystalline and amorphous materials differ by a factor of 40 in specific surface area, and the intensity per unit mass of the sharp surface silanol band near 3745 cm-1 in the amorphous material is an order of magnitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(50 citation statements)
references
References 29 publications
(18 reference statements)
5
43
0
Order By: Relevance
“…To exclude the effect of surfactant on the cytotoxicity, the surfactant CTAB was removed completely by calcinations, which was supported by the absence of characteristic IR bands between 2800–3000 cm −1 (Figure 7). It is generally thought that the calcination of silica would result in the cytotoxicity reduction due to the absence of surface radicals and the onset of hydrophobicity 46–49. However, it is not known, as far as we know, if the calcination of spherical MS particles has similar effects on the cytotoxicity of common silica particles, and what is the pure relationship between the cytotoxicity and particle size of spherical C‐MS particles.…”
Section: Resultsmentioning
confidence: 99%
“…To exclude the effect of surfactant on the cytotoxicity, the surfactant CTAB was removed completely by calcinations, which was supported by the absence of characteristic IR bands between 2800–3000 cm −1 (Figure 7). It is generally thought that the calcination of silica would result in the cytotoxicity reduction due to the absence of surface radicals and the onset of hydrophobicity 46–49. However, it is not known, as far as we know, if the calcination of spherical MS particles has similar effects on the cytotoxicity of common silica particles, and what is the pure relationship between the cytotoxicity and particle size of spherical C‐MS particles.…”
Section: Resultsmentioning
confidence: 99%
“…Although evidence exists that links silica surfaces and hydroxyl radicals to hemolytic activity, it has not yet been shown that free radicals result from the silica-cell membrane contact. Results of our previous research (7) suggest that this issue merits further investigation. The interaction of silica with cell membranes may produce free-radical species and cause the subsequent penetration of these radicals into the cell.…”
Section: Introductionmentioning
confidence: 85%
“…These authors demonstrated that the hydrogen bonding of polyvinyl-N-oxide (PVPNO) with silanol groups, as well as the bonding of metal cations to the ionized SiOgroups, results in significant decreases in hemolytic activity. Furthermore, it has been found that the complete removal of surface hydroxyl groups from the surface of respirable silica particles nearly eliminates the hemolytic potential of silica (7), suggesting that hydroxyl groups might be involved in other cytotoxic processes associated with silica-induced lung injury.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, SGPs had very difficult shapes for both uptake by phagocytes and circulation in the body. 31,32 Phagocytes are of crucial importance for maintaining healthy tissues because they remove the host's dead (or dying) and damaged cells as well as foreign bodies. 28,[33][34][35] Although both RAW264.7 (peritoneal) and MH-S (alveolar) cells are mouse macrophage cell lines, they express different receptors that can interact with cytotoxic and helper T cells, respectively, and MH-S cells contain very low levels of lysozymes compared to RAW264.7 cells.…”
Section: Discussionmentioning
confidence: 99%